Inovasi Pakan Organik pada Ternak Ayam Kampung Super: Organic Feed Innovation for Super Village Chicken Livestock - Sitti Rosmalah; Syamsinar Syamsinar; Basri Sufa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Public nutrition is essential to obtain a healthy and fit body condition, especially during a pandemic like today. The content of vitamins A, C, magnesium, gelatin, phosphorus, and antioxidants in chicken meat can help build the immune system to fight viruses. Besides that, the content of amino acids derived from chicken protein can form antibodies to fight infections. Therefore, raising free-range chickens can be a good business opportunity to fulfill the need for healthy meat from free-range chickens. In addition, it is indicated that the demand for chicken meat in Kendari has yet to be fulfilled, so it must be supplied from other regions. Therefore, raising super free-range chickens can be a promising solution and business opportunity with a maintenance pattern that is not too complicated, where even a not-too-large area of ​​land can be used as a place for its maintenance. Even so, the obstacle free-range chicken breeders face is the slow growth of free-range chickens, which can take 4-6 months to produce 1 kg body weight. But now, this problem can be overcome by the presence of super-free-range chickens or super Javanese chickens, which are the result of crosses between male local native chickens and breeder breeders that have fast growth characteristics. With a maintenance pattern that is not too complicated, where even a not-too-large area of ​​land can be used as a place for its maintenance. The body and flesh still show the type of free-range chicken but with organic care, without drugs, and with organic feed.